Оранжевый абажур: три повести о тридцать седьмом / Георгий Демидов - Демидов Георгий Георгиевич (Memoria, 2009)
Экземпляры: ф. 1 (20131101) / Инвентарный номер: 100235 / Цена: 50.00 / Авт.знак: Д 30 / ББК: 84(2Рос=Рус)6